Dualisme Pengaturan Sanksi terhadap Wajib Pajak Berdasarkan Undang-Undang Ketentuan dan Tata Cara Umum Perpajakan - Ariska Cesar Divian Candra Kusuma; Kartika Youri Widodo (CV Rewang Rencang, 2025)
Indonesia’s taxation system faces regulatory dualism in imposing sanctions, involving both administrative and criminal measures under the Law on General Provisions and Tax Procedures (UU KUP), which may expose taxpayers to double jeopardy. Adopting a normative legal approach, this study examines the normative gaps in defining state revenue losses and highlights the legal uncertainty in delineating administrative violations from criminal offenses. The current framework risks overcriminalization and undermines the principle of ultimum remedium. This paper advocates for regulatory reform by clarifying the parameters of state losses and applying the una via principle to ensure legal certainty and proportional sanction enforcement.